Novel potential pharmacological applications of dimethyl fumarate—an overview and update - Bresciani, Giorgia; Manai, Federico; Davinelli, Sergio; Tucci, Paolo; Saso, Luciano; Amadio, Marialaura (Frontiers in Pharmacology, 2023)
Dimethyl fumarate (DMF) is an FDA-approved drug for the treatment of psoriasis and multiple sclerosis. DMF is known to stabilize the transcription factor Nrf2, which in turn induces the expression of antioxidant response element genes. It has also been shown that DMF influences autophagy and participates in the transcriptional control of inflammatory factors by inhibiting NF-κB and its downstream targets. DMF is receiving increasing attention for its potential to be repurposed for several diseases. This versatile molecule is indeed able to exert beneficial effects on different medical conditions through a pleiotropic mechanism, in virtue of its antioxidant, immunomodulatory, neuroprotective, anti-inflammatory, and anti-proliferative effects. A growing number of preclinical and clinical studies show that DMF may have important therapeutic implications for chronic diseases, such as cardiovascular and respiratory pathologies, cancer, eye disorders, neurodegenerative conditions, and systemic or organ specific inflammatory and immune-mediated diseases. This comprehensive review summarizes and highlights the plethora of DMF's beneficial effects and underlines its repurposing opportunities in a variety of clinical conditions.The following work is a comprehensive review of current preclinical and clinical evidence on the broad spectrum of intriguing potential therapeutic applications of dimethyl fumarate, whose mechanisms of action and current clinical uses are also detailed. This review is unique in the variety of the pathologies it examines, gathering relevant studies in the cardiovascular, respiratory and neurodegenerative contexts, in ocular and gastrointestinal diseases, in cancer and other miscellaneous pathologies.